From Dissatisfaction to Devotion: The Amplifying Role of Brand Love in Recovery Satisfaction and Repurchase Intentions Within Indonesia's Local Fashion Sector - Rohim, Abdul; Kurniawati, Kurniawati; Risqian, Renny (Jurnal Bisnis dan Manajemen, 2026)
This study aims to investigate the factors that sustain and enhance repurchase intention among consumers of local fashion brands in Indonesia. We posit that to foster continuous patronage, local entrepreneurs must prioritize customer satisfaction derived from past purchasing experiences, while also ensuring high product quality and competitive pricing. These elements are hypothesized to cultivate brand love, an emotional attachment that subsequently drives repeat purchases. Employing a quantitative approach, this study utilizes hypothesis testing on cross-sectional data gathered via an online survey with a Likert scale. The population comprises young adult consumers (aged 18 and above) who have purchased products from local fashion brands at least three times within the last six months. The findings confirm a significant positive relationship between recovery satisfaction and repurchase intention. Furthermore, product quality is shown to positively influence brand love, which in turn, positively affects repurchase intention. The analysis also reveals that brand love acts as a significant moderator, strengthening the association between recovery satisfaction and repurchase intention. From a managerial perspective, it is crucial to actively solicit and respond to customer feedback, maintain positive communication, ensure approachability, and demonstrate empathy. Strengthening brand love through consistent, positive customer experiences is essential for building a robust brand identity. This study recommends that future research explore additional variables influencing repurchase intention, such as brand trust, brand experience, and brand loyalty. The findings herein provide a foundation for evaluating consumer behavior patterns within the broader apparel and accessories market.